2021
DOI: 10.1021/acs.estlett.1c00359
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pyrrole–DNA Adducts Define the Early Tumorigenic Risk in Patients with Pyrrolizidine Alkaloid-Induced Liver Injury

Abstract: Pyrrolizidine alkaloids (PAs) are among the most common phytotoxins with emerging evidence to contaminate soil, water, and nearby plants. Humans are frequently exposed to PA-contaminated food products or PA-containing herbal remedies. The reactive metabolites of PAs rapidly alkylate DNA to form pyrrole–DNA adducts (PDAs) and seed a population of mutations that initiate tumorigenesis in experimental models. However, the clinical evidence of PA-induced initial DNA damage is absent. This study developed a liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Increasing evidence suggests that PA exposure biomarkers, such as pyrrole-protein adducts, pyrrole-DNA adducts, and pyrrole-amino acid adducts, are specific and applicable diagnostic biomarkers. This evidence supports the causality assessment used in the updated RUCAM [27,[41][42][43]. Therefore, for future clinical diagnosis of suspected PA-induced HSOS cases, the RUCAM, the Nanjing criteria, and specific PA exposure biomarkers should be applied together to confirmatively diagnose PA-induced HSOS cases.…”
Section: Discussionsupporting
confidence: 69%
“…Increasing evidence suggests that PA exposure biomarkers, such as pyrrole-protein adducts, pyrrole-DNA adducts, and pyrrole-amino acid adducts, are specific and applicable diagnostic biomarkers. This evidence supports the causality assessment used in the updated RUCAM [27,[41][42][43]. Therefore, for future clinical diagnosis of suspected PA-induced HSOS cases, the RUCAM, the Nanjing criteria, and specific PA exposure biomarkers should be applied together to confirmatively diagnose PA-induced HSOS cases.…”
Section: Discussionsupporting
confidence: 69%
“…They reported that increase of electrospinning duration and thickness of the air filters enhanced coronavirus aerosol removal (99.9% and 99.1% for PVDF 30 and PVDF 20 , respectively), though there was a marginal decrease of the pore size of PVDF 30 compared to PVDF 20 . Polyelectrolyte coating did not promote electrospun air filters for removing coronavirus aerosols, and the average filtration efficiency for PVDF 20 /PEI and PVDF 20 /PVPA was 99.1% and 95.7%, respectively [ 62 ]. Also, Shen et al a homogeneous electrospinning dope solution containing of polyvinylidene difluoride (PVDF) and a dye photosensitizer in N,N -dimethylformamide/acetone was electrospun onto one layer of polypropylene (PP) fabrics (basic protection face mask).…”
Section: Introductionmentioning
confidence: 99%
“…This injury is confirmatively diagnosed by blood pyrrole-protein adducts, which are specific diagnostic biomarkers, supporting the causality evaluation using the updated Roussel Uclaf Causality Assessment Method (RUCAM) ( Danan and Teschke, 2016 ; Teschke and Danan, 2020 ). Furthermore, our recent study discovered an unexpectedly extensive implication of PA exposure in patients with liver cancer, providing a clinical indication of PA-associated liver cancer ( He et al, 2021c ).…”
Section: Introductionmentioning
confidence: 99%